PERAN NON-GOVERNMENTAL ORGANIZATION (NGO) DALAM PENGUATAN TATA KELOLA PEMERINTAHAN MELALUI KOLABORASI PENTA HELIX DI KABUPATEN BONE. - Heri Afian; Muh Sawir (Universitas Cahaya Prima, 2026)
This study analyzes the role of Non-Governmental Organizations (NGOs) in strengthening governance through Penta Helix collaboration in Bone Regency. This research uses a qualitative approach with a case study design, with data collection techniques including in-depth interviews, field observations, and documentation studies involving NGOs, local governments, communities, academics, the business world, and the media. The research results show that NGOs have a strategic role in strengthening community participation, acting as a liaison for policy communication between the government and the community, carrying out social oversight functions regarding the implementation of public policies, and acting as partners in the implementation of development programs. However, this role has not yet been fully institutionalized and tends to take place in unequal relations, with limited data access, and weak coordination across actors. The Penta Helix collaboration in Bone Regency is still in the coordination stage and has not yet achieved an integrated co-creation model. Based on analysis using the theories of Ansell and Gash (2008) and Emerson et al. (2012), collaborative governance in Bone Regency is in the nascent to emerging collaborative governance regime phase . Institutional strengthening, increased transparency, and the establishment of formal collaboration forums are essential to improving the effectiveness of local governance.